Healthy Eating: Folate - Linda B. Bobroff (EDIS)
Folate is one of the B vitamins. It is involved in the formation of DNA, the genetic material found in all cells of your body. Folate is an important nutrient for everyone. It is especially important for pregnant and nursing women, growing children, and older adults. Health problems may result if people do not get enough folate. This revised 2-page fact sheet was written by Linda B. Bobroff and published by the UF Department of Family, Youth and Community Sciences, October 2012.